Mein Leben : [Oberbefehlshaber der deutschen Kriegsmarine 1935 - 1943] - Raeder, Erich 1876-1960 (Bublies, 2009)
Enth.: Bd. 1. Bis zum Flottenabkommen mit England 1935. - Bd. 2. Von 1935 bis Spandau 1955